2019
DOI: 10.3390/w11050954
|View full text |Cite
|
Sign up to set email alerts
|

Distributive Characteristics of Riverine Nutrients in the Mun River, Northeast Thailand: Implications for Anthropogenic Inputs

Abstract: The nutrient contents of Mun River water in northeast Thailand during the dry season were measured to investigate the effect of human activities on dissolved load species. Dissolved organic carbon (DOC) values varied from 2.5 to 17.1 mg/L, averaging 9.0 mg/L; dissolved inorganic nitrogen (DIN) ranged between 0.12 and 0.11 mg/L; Cl− values ranged from 1.7 to 668.6 mg/L, with an average value of 84.8 mg/L; dissolved silicon (DSi) varied from 1.7 to 9.9 mg/L; and SO42− values averaged 8.9 mg/L. DOC, Cl−, and SO42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…In the sample site LCJ-1, 3.8% of the total cations are derived from the rain inputs, while the contributions of the halite dissolution, gypsum dissolution, silicate weathering and carbonate weathering make up 19.2%, 24.7%, 17.4% and 34.9% of the total cations, respectively. Similar to many studies [5,6,7,8,12,13], the carbonate weathering is the predominant sources of the riverine solutes. As mentioned before, the estimate regarding the contribution of gypsum should be the maximum value because this estimated contribution value involves the contribution of sulfate oxidation to the SO 4 2 − .…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…In the sample site LCJ-1, 3.8% of the total cations are derived from the rain inputs, while the contributions of the halite dissolution, gypsum dissolution, silicate weathering and carbonate weathering make up 19.2%, 24.7%, 17.4% and 34.9% of the total cations, respectively. Similar to many studies [5,6,7,8,12,13], the carbonate weathering is the predominant sources of the riverine solutes. As mentioned before, the estimate regarding the contribution of gypsum should be the maximum value because this estimated contribution value involves the contribution of sulfate oxidation to the SO 4 2 − .…”
Section: Resultssupporting
confidence: 63%
“…Because Cl − is conservative in river, the Cl − contents in river water derived from rain should keep the same level. The widely accepted method is assuming that the sample with the lowest Cl − concentration acquired all its dissolved Cl − completely from the atmospheric inputs, thus other ions derived from the rain can be calculated by the elemental ratio in rain [5,6,7,8,9,12,13,14]:[X] rain = [Cl] lowest × (X/Cl) rain where [X] rain is the element X concentrations in rain waters, [Cl] lowest is the concentrations of Cl − which is assumed completely from the precipitation, (X/Cl) atm is the X/Cl − molar ratio in rain waters. The sample LCJ-25 (Langcangjiang River-25) with the lowest Cl − concentration (3.5 μmol/L) is collected in the tributaries in pristine areas, the bedrock in the sampling site LCJ-25 is Precambrian rocks consisting of medium-highly granodioritic-granitic metamorphic rocks, in which the chloride contents are limited.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data of REE in soils quoted from the previous study, and the information of six soil profile location and REE analysis can be found in Zhou et al (2020) . The dissolved organic carbon (DOC) concentrations of river water quoted from Liu et al (2019) .…”
Section: Methodsmentioning
confidence: 99%
“…The monthly average temperature is from 25 to 30 °C [25], and the highest temperature is in April. The fluvial deposit area where the Mun River flows through is primarily dominated by cretaceous claystone and sandstone with some halite and gypsum spread around the basin, while there is less than 10% coverage of tertiary basalt in the south of basin [22,26].…”
Section: Methodsmentioning
confidence: 99%